Sporoderm ultrastructure of some Devonian and Permian representatives of Biharisporites and their botanical affinity. (2nd October 2022) - Kanarkina, Alina; Zavialova, Natalia; Orlova, Olga; Joshi, Arun
Abstract: The megaspore genus Biharisporites has a very wide stratigraphic range, being recorded from the Devonian to the Cretaceous. However, in situ these megaspores are known only from the Middle–Upper Devonian, from archaeopteridalean sporangia. Post-Devonian producers of Biharisporites are so far unknown; the parent group can only be hypothesized from the spore morphology and ultrastructure, and from the composition of contemporaneous assemblages of macroremains. To contribute to the understanding of the botanical affinity of dispersed megaspores of the genus, we undertook a comparative ultrastructural study of several Biharisporites species from the Middle Devonian of Russia and the Lower Permian of India. Surprisingly, we found exclusively lycopsid variants of the sporoderm ultrastructure not only in the Permian spores, but also in the Devonian. Therefore, some megaspores of Biharisporites were produced by lycopsids even in the Middle Devonian. Megaspores of Biharisporites morphology have been produced by different groups of spore-bearing plants since the Middle Devonian, and the genus Biharisporites is heterogeneous.